Peningkatan Pemahaman Materi Fiqih: Optimalisasi Penggunaan Media Grafis dalam Pembelajaran - Tauhid, Moh.; Komariah, Komariah (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2024)
The aim of this research is to analyze the use of graphic media in fiqh learning, and analyze the results of students' learning understanding through the use of graphic media in fiqh learning. The classroom action research method is a relevant method to use in this research. The result is that using graphic media makes students enthusiastic about the learning process, carrying out presentations and group discussions and making summaries in accordance with language rules and systematic explanations. Next, the results of students' learning understanding after using graphic media in fiqh learning can make it easier for students to understand fiqh subject matter as evidenced by the increase in student learning outcomes in fiqh subjects from one cycle to the next. Student learning outcomes in the first cycle were an average of 74.16, in the second cycle it increased to 79.16. while in the last cycle the student learning outcomes were 83.95. In this way, the use of graphic media in fiqh learning can facilitate students' understanding.